2017
DOI: 10.1016/j.jagp.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Response to a 24-Month Physical Activity Intervention in Sedentary Older Adults

Abstract: BACKGROUND Greater hippocampal volume is observed in healthy older adults after short-term structured exercise. Whether long-term exposure to real-world physical activity (PA) programs has similar effects for sedentary older adults with impaired mobility and comorbid conditions is not known. HYPOTHESIS A long-term moderate intensity regimen of PA is related to larger volume of the hippocampus in older adults at risk for mobility disability. We further explore whether these associations are modified by factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
68
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 30 publications
7
68
0
2
Order By: Relevance
“…Specifically, we found that the average individual in our sample (aged 82.5 years at first MRI) demonstrated a 6.2% reduction in bilateral hippocampal volume over 3 years, whereas individuals who had maintained walking over the previous decade (based on a slope value 1 SD above the mean) demonstrated a 4.5% reduction in bilateral hippocampal volume. Although previous studies have shown that PA— including walking—might mitigate hippocampal atrophy, our study adds to the literature by showing that this mitigation effect is not restricted to individuals under the age of 80 (Bugg and Head, 2011; Erickson et al, 2011; Makizako et al, 2015; Rosano et al, 2016; Ten Brinke et al, 2014). Our results also add to the literature by suggesting that walking effects on hippocampal structure might primarily involve macro- rather than microstructural protection, as there was no evidence that regular walking had an impact on changes in hippocampal MD.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Specifically, we found that the average individual in our sample (aged 82.5 years at first MRI) demonstrated a 6.2% reduction in bilateral hippocampal volume over 3 years, whereas individuals who had maintained walking over the previous decade (based on a slope value 1 SD above the mean) demonstrated a 4.5% reduction in bilateral hippocampal volume. Although previous studies have shown that PA— including walking—might mitigate hippocampal atrophy, our study adds to the literature by showing that this mitigation effect is not restricted to individuals under the age of 80 (Bugg and Head, 2011; Erickson et al, 2011; Makizako et al, 2015; Rosano et al, 2016; Ten Brinke et al, 2014). Our results also add to the literature by suggesting that walking effects on hippocampal structure might primarily involve macro- rather than microstructural protection, as there was no evidence that regular walking had an impact on changes in hippocampal MD.…”
Section: Discussionmentioning
confidence: 62%
“…Intervention studies have shown that structured exercise training—e.g. in the form of walking programs—increases cortical and hippocampal gray matter volume (Colcombe et al, 2006; Erickson et al, 2011; Rosano et al, 2016; Ten Brinke et al, 2014) and that training-induced improvements in aerobic fitness correlate with improved microstructural integrity (Voss et al, 2013) among previously sedentary older adults. PA-related structural changes in the brain have also been associated with improved cognitive health, including memory performance (Erickson et al, 2011) and a lower risk of cognitive impairment (Erickson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…People with a history of a physically active lifestyle are known to have some resilience to the effects of normal aging on cognition. In humans, the correlation between aerobic exercise and improved cognition is strong and exercise appears to be effective across the lifespan (Chaddock et al, 2010;Erickson et al, 2011;Herting & Nagel, 2012;Kleemeyer et al, 2016;Rosano et al, 2017;Stillman et al, 2018;Thomas et al, 2016). This has significant implications for older adults who face heightened risk of dementia (Erickson et al, 2011;Kleemeyer et al, 2016;Rosano et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of exercise on cognition has been linked with hippocampal function (Rubin, Watson, Duff, & Cohen, 2014), which is important for spatial tasks and cognitive flexibility (Burghardt, Park, Hen, & Fenton, 2012). Although many studies highlight changes in the hippocampus volume and connectivity as the neural correlate for exercise effects in humans (Chaddock et al, 2010;Erickson et al, 2011;Herting & Nagel, 2012;Kleemeyer et al, 2016;Rosano et al, 2017), the molecular correlates are poorly understood. Rodent models have been useful in this regard and have provided additional insights.…”
Section: Introductionmentioning
confidence: 99%